2013
DOI: 10.1590/s0100-204x2013001200007
|View full text |Cite
|
Sign up to set email alerts
|

Ruzigrass affecting soil-phosphorus availability

Abstract: -The objective of this work was to evaluate the effectiveness of ruzigrass (Urochloa ruziziensis) in enhancing soil-P availability in areas fertilized with soluble or reactive rock phosphates. The area had been cropped for five years under no-till, in a system involving soybean, triticale/black-oat, and pearl millet. Previously to the five-year cultivation period, corrective phosphorus fertilization was applied once on soil surface, at 0.0 and 80 kg ha -1 P 2 O 5 , as triple superphosphate or Arad rock phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
11
0
4
Order By: Relevance
“…This increase in TP content may be related to the predominant vegetation in these areas; for example, the site at Onça Puma 3, vegetated with Marandu grass (Brachiaria brizantha), which has a high demand for P and high biomass production that favours incorporation of the element into the plant tissue and increases organic residue and reserves in the soil (DUDA et al, 2013;MERLIN;HE;ROSOLEM, 2013). Studies by Nogueira et al (2008) showed no difference between the Pol fraction in an area of native forest and an area of intensive farming, where the spontaneous growth of grass in the latter area may have facilitated the maintenance of OM in the soil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in TP content may be related to the predominant vegetation in these areas; for example, the site at Onça Puma 3, vegetated with Marandu grass (Brachiaria brizantha), which has a high demand for P and high biomass production that favours incorporation of the element into the plant tissue and increases organic residue and reserves in the soil (DUDA et al, 2013;MERLIN;HE;ROSOLEM, 2013). Studies by Nogueira et al (2008) showed no difference between the Pol fraction in an area of native forest and an area of intensive farming, where the spontaneous growth of grass in the latter area may have facilitated the maintenance of OM in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazilian soils, such as Latosols, P is present mainly in forms which are unavailable to plants (GUERRA et al, 1996;MERLIN;HE;ROSOLEM, 2013), especially forms of inorganic P with highenergy binding to the mineral fraction and to stable organic forms (EBERHARDT et al, 2008;NOVAIS;SMYTH, 1999;SÁNCHEZ-ALCALÁ et al, 2014). After fertilization of these soils with superphosphate, around 85 to 90% of the P is unavailable to plants during the first year of application due to adsorption and precipitation with Fe, Al and Ca (GICHANGI;MNKENI;BROOKES, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, Pacheco et al (2013) relataram o acúmulo de N, P e K pelas plantas de U. ruziziensis, que é importante na ciclagem desses nutrientes e para a disponibilidade a culturas sucessoras. Merlin et al, 2013 relatam que o cultivo de U. ruziziensis aumentou os teores de P no solo, assim como o seu conteúdo nas folhas da soja que sucedeu a forrageira.…”
Section: Resultsunclassified
“…Merlin et al (2013), objetivando verificar a eficácia da Urochloa ruziziensis em aumentar a disponibilidade de P, em solo de áreas fertilizadas com superfosfato triplo ou fosfato Arad, observou que o cultivo da braquiária proporcionou incrementos das diversas formas de P no solo, principalmente das mais lábeis, bem como do conteúdo de P nas folhas da soja, independentemente da fonte de P utilizada. No entanto, a produtividade da soja não aumentou pela introdução da braquiária no sistema de cultivo.…”
Section: P-lábil P-pouco Lábil E P-não Lábil Aos 30 Dias Após Semeadunclassified
“…Resultados de pesquisas têm mostrado que o uso de plantas forrageiras, como capim braquiária e milheto, entre outras, proporcionam reciclagem de nutrientes, com destaque para o P, pois de acordo com Merlin et al (2013), essas plantas são capazes de absorver formas de P não-lábeis e,ou, não detectadas pelos métodos tradicionais de análise de solo, tornando-o disponível para as culturas em sucessão.…”
Section: Introductionunclassified